The Effect of Applying an Online Learning System on Islamic Religious Education and the Characteristics of Learning Media Use - Unang Wahidin; Agus Mailana; M Sarbini; Wulan Anggraeni; Taufiq Nur Azis (STAI Hubbulwathan Duri, 2023)
The current deployment of the online learning system is novel for educators and students, and it starkly contrasts the more traditional face-to-face model of education. This research aims to ascertain if and how an online learning system influences the utilisation of learning media in the context of Islamic theological and moral instruction. The study takes a quantitative, survey-based approach; data were gathered using questionnaires, records, and relevant literature reviews; descriptive statistics were used to analyse the results. The application of the online learning system has a significant effect on Islamic religious education subjects and character education through the use of learning media, as determined by the product-moment correlation test, the correlation test of determination, and the significance test. The following is the description: The Rcount value of 0.61 is greater than the Rtable value of 0.294 with a significant level of 5% in the strength of influence test, indicating that Rcount Rtable (0.61 0.294) means Ha is accepted and H0 is rejected. While the coefficient of determination test results is 37.21%, the significant correlation test results are 0.43, indicating a moderate correlation coefficient.